"EGO" OF MONTAIGNE THROUGH PERSONALLY CONSTITUTED INTERNAL EXPERIENCE - Kurbanov Umidjon (Galaxy International Interdisciplinary Research Journal, 2021)
The article is devoted to a critical analysis of the philosophy of M. Montaigne and his "Experiments" in the aspect of a person’s comprehension of himself. It is argued that the main essence of Montaigne’s "Experiments" is, according to the author, in an attempt to set up experiments on himself and his own mind in order to comprehend a person himself.